Taken in Texas - Sleeman, Susan (Love inspired suspense., 2019)
"Working her first case as deputy sheriff with her ex-boyfriend, Detective Cord Goodwin, Kendall McKade is determined to track the kidnappers--even if it makes her a target. Desperate to find the abducted victim, his aunt, Cord must keep Kendall safe...while also caring for his recently orphaned nephew. Teaming up threatens to rekindle Cord and Kendall's relationship, but first they must solve a life-threatening mystery." -- Page [4] cover.